Book Review: “Chasing Dignity”: Rachhpal Sahota - Dhir, Simrita (Sikh Research Journal, 2024)
Rachhpal Sahota’s novel Chasing Dignity is a compelling narrative, set in the 1980s and ‘90s in Punjab, India, tracing the many twists and turns in the life of a low caste boy, Jaggi. The Indian caste system is a social stratification system characterized by hereditary status and endogamy, enforcing crippling social barriers for those on the lower end of that spectrum. Bound by this rigid system of social hierarchy, Jaggi, a Keera, faces many hurdles as he sets out on his pursuit of a successful life. In the story, his mother Bindo, and his friends, Navi and Rani, serve as catalysts on this journey.